Choreography Form Of Kiprah Balun Lamongan Dance In The 2019 East Java Dance Works Festival - Junessa, Eggy; yanuartuti, setyo (Solah, 2025)
Kiprah Balun Dance is a dance work in Lamongan that has been developed from Kiprah Balun Dance with uniqueness in its choreography. This study aims to analyze and describe the choreography form of Kiprah Balun Dance in Lamongan 2019 in the East Java Dance Works Festival. This study used a qualitative descriptive research method, with data collection techniques using interviews, observations, and documentation studies. Data analysis techniques consist of stages of reduction, data presentation, and drawing conclusions. The results of the study show that the Kiprah Balun dance has a concept that describes a human being who is born to earth, he learns, and improves himself as a provision to play a role in the community. The conclusion of this study is that the 2019 Kiprah Balun dance still represents the Kiprah Bahlun dance with characteristic movement structures which are then strengthened by a musical atmosphere.